A general mechanism of KCNE1 modulation of KCNQ1 channels involving non-canonical VSD-PD coupling - Xiaoan Wu (Nature Portfolio, 2021)
Wu et al. demonstrate that KCNE1 exerts its effects on potassium channel KCNQ1 function by regulating the coupling between the voltage-sensing domain and pore domain via KCNE1-induced rotation. As a consequence of this rotation, residue clashes occur that prohibit the formation of a conductive intermediate state conformation of the voltage sensor.